Implementasi Load Balancing Pada Server Dengan Menggunakan Algoritme Least Traffic Pada Software Defined Network - Nur Fauzi; Widhi Yahya; Adhitya Bhawiyuga (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
On the use of the computer network technology continues to evolvefrapidly. One of the solutions to these problems are Software defined network liquid separating the concept of control plane and data plane. Control plane SDN is programmed allows to implement a wide range of applications, including network load balancing. Load balancing server performance Test liquid distribution in mere play every request and divides the incoming requests to be given to a server by providing the same service. There are several algorithms of load balancing that is used in one round-robin algorithm, but the algorithm does not pay attention to the traffic. An important aspect of liquid traffic to choose the path the sound server. In this research. A load balancing algorithm is used in this researchis the Algorithm a little traffic the algorithm allocates liquid special lines to the server with the shortest traffic. This algorithm will be tested and performance analyzed. This test is used in the test is has the functionality, throughput, packet loss, and time korvegensi. On testing the functionality of server-mapping algorithms a bit traffic handling big demand from the clients is better than a round-robin algorithm because the algorithm at least traffic would not choose the path to the server that there is a burden of the past Cross and will choose the path to another server. Throughput testing of the algorithm a little traffic is superior compared to the round robin algorithm on a high category. While the Pack lost the roud robin has an average of 6.96% higher than little traffic with an average of 2.97%. On the results of the test of convergence, convergence time is the time gained Round Robin Algorithm is 10.51 seconds compared to 14.80 seconds time obtained the algorithm a little traffic